Implementing nitrous oxide cracking technology in the labour ward to reduce occupational exposure and environmental emissions: a quality improvement study*. (15th September 2022) - Pinder, A.; Fang, L.; Fieldhouse, A.; Goddard, A.; Lovett, R.; Khan‐Perez, J.; Maclennan, K.; Mason, E.; MacCarrick, T.; Shelton, C.
Summary: Nitrous oxide, a potent greenhouse gas, is a common labour analgesic. One method which may reduce its carbon footprint is to 'crack' the exhaled gas into nitrogen and oxygen using catalytic destruction. In this quality improvement project, based on environmental monitoring and staff feedback, we assessed the impact of nitrous oxide cracking technology in the maternity setting. Mean ambient nitrous oxide levels were recorded during the final 30 minutes of uncomplicated labour in 36 cases and plotted on a run chart. Interventions were implemented in four stages, comprising: stage 1, baseline (12 cases); stage 2, cracking with nitrous oxide delivered and scavenged via a mouthpiece (eight cases); stage 3, cracking with nitrous oxide via a facemask with an air‐filled cushion (eight cases); stage 4, cracking with nitrous oxide via a low‐profile facemask, and enhanced coaching on the use of the technology (eight cases). The median ambient nitrous oxide levels were 71% lower than baseline in stage 2 and 81% lower in stage 4. Staff feedback was generally positive, though some found the technology to be cumbersome; successful implementation relies on effective staff engagement. Our results indicate that cracking technology can reduce ambient nitrous oxide levels in the obstetric setting, with potential for reductions in environmental impacts and occupational exposure.